Effects of genetic factors to stent thrombosis due to clopidogrel resistance after coronary stent placement - Kirac, D; Erdem, A; Avcilar, T; Yesilcimen, K; Guney, A I; Emre, A; Yazici, S; Terzi, S; Kaspar, E C; Cetin, S E; Isbir, T (Cellular and Molecular Biology, 2016)
Stent thrombosis (ST) is considered as a multifactorial problem which is mostly occurs due to clopidogrel resistance. It may be due to some CYP450 enzyme deficiencies which play role in clopidogrel metabolism. Therefore the aim of this study is to detect the mutations in CYP2C19 and CYP2C9 genes which may cause ST, and to investigate the relation between other risk factors and ST. 50 individuals who have stent thrombosis and 50 individuals who haven't got any complication were enrolled as patient and control group respectively. *2,*3,*4,*5,*17 mutations in CYP2C19 gene and *2 ve *3 mutations in CYP2C9 gene were investigated with RT-PCR. Clopidogrel and aspirin resistance were investigated with multiple electrode platelet aggregometry. Results were evaluated statistically. CYP2C19*2 mutation was found statistically higher in patients (% 18), whereas CYP2C19*17 was found statistically higher in controls (% 36)(p<0.05). Additionally, it was found that patients who have clopidogrel and/or aspirin resistance also have CYP2C19*1/*2 or CYPC19*2/*2 genotype. These relations were also found statistically significant. (p=0,000005 for clopidogrel resistance and p=0,000059 for aspirin resistance). In conclusion, it was suggested that there is a relation between CYP2C19*2 mutations and ST due to clopidogrel resistance, and CYP2C19*17 may have a protective role in this process. The use of novel and more potent drug or high clopidogrel maintenance dosing before stent implantation may be beneficial treatment options for antiplatelet therapy in CYP2C19*2 carriers.